Optimization of the Medium Components for Recombinant Nattokinase Production by Bacillus Subtilis BD170 - Ngo Thi Tuong, Chau (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 1SDO - 10.25073/2588-1094/vnuees.4163, 2017)
Nattokinase is a serine protease with fibrinolytic activity whose clinical efficacy and safety for human by the oral route has been proven. In present study, we optimized the medium components for recombinant nattokinase production by Bacillus subtillis DB170. Carbon, nitrogen and mineral sources suitable for the recombinant nattokinase production were maltose, soybean, MgSO 4 and NaCl, respectively. These factors were subsequently optimized by using the response surface methodology (RSM). The obtained results showed the optimal medium components for the nattokinase biosynthesis contained 15 g/l maltose, 45 g/l soybean, 0.75 g/l MgSO 4 and 0.75 g/l CaCl 2 . After 48 hrs of fermentation at initial pH 7.0, nattokinase activity reached the highest level of 342 FU/ml, 1.3 folder higher than that in the pre-optimized one.